2011
DOI: 10.1073/pnas.1010331108
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale mechanical properties of Xenopus embryonic epithelium

Abstract: Epithelia are planar tissues that undergo major morphogenetic movements during development. These movements must work in the context of the mechanical properties of epithelia. Surprisingly little is known about these mechanical properties at the time and length scales of morphogenetic processes. We show that at a time scale of hours, Xenopus gastrula ectodermal epithelium mimics an elastic solid when stretched isometrically; strikingly, its area increases twofold in the embryo by such pseudoelastic expansion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 36 publications
10
64
2
Order By: Relevance
“…5B). Cells are considered to exert an elastic restoring force to maintain cell appearance (Luu et al, 2011;Nagai and Honda, 2001). Vertices were assumed to move to maintain the length of the basal edge and cell perimeter based on our morphometric results (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5B). Cells are considered to exert an elastic restoring force to maintain cell appearance (Luu et al, 2011;Nagai and Honda, 2001). Vertices were assumed to move to maintain the length of the basal edge and cell perimeter based on our morphometric results (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous biomechanical analyses of gastrula stages in Xenopus embryos (Beloussov et al, 2006;Zhou et al, 2009Zhou et al, , 2010von Dassow et al, 2010von Dassow et al, , 2014Luu et al, 2011) have suggested that mechanical feedback mechanisms operate during development to allow robust morphogenetic movements. Force production in dorsal tissues is needed to deform both those tissues and the rest of the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue explants, after having rounded up under the influence of surface tension, deviate from a spherical equilibrium shape due to gravity. We used this effect to determine tissue surface tension σ (Del Rio and Neumann, 1997; David et al, 2009;Luu et al, 2011) as a measure of cohesion (Box 1, Fig. 1A, Table 1; supplementary material Fig.…”
Section: Relationship Between Tissue Surface Tension and Tissue Viscomentioning
confidence: 99%
“…1B; supplementary mathematical analyses, Section 2). Observation started about 20 min after excision, when explants had taken on ellipsoidal shapes, and elastic (von Dassow and Davidson, 2009;Luu et al, 2011) and wounding (Li et al, 2013) reactions had subsided. Rounding was associated with cell rearrangement ( Fig.…”
Section: Relationship Between Tissue Surface Tension and Tissue Viscomentioning
confidence: 99%
See 1 more Smart Citation